Failure of enhanced recovery after surgery in liver surgery: a systematic review and meta analysis - Ren, Qiuping; Wu, Menghang; Li, Hong Yu; Li, Jiafei; Zeng, Zi Hang (Frontiers in Medicine, 2023)
Purpose This study aimed to conduct a systematic review of the literature to identify and summarize the existing evidence regarding ERAS failure and related risk factors after hepatic surgery. The objective was to provide physicians with a better understanding of these factors so that they can take appropriate action to minimize ERAS failure and improve patient outcomes. Method A literature search of the PubMed MEDLINE, OVID, EMBASE, Cochrane Library, and Web of Science was performed. The search strategy involved terms related to ERAS, failure, and hepatectomy. Result A meta-analysis was conducted on four studies encompassing a total of 1,535 patients, resulting in the identification of 20 risk factors associated with ERAS failure after hepatic surgery. Four of these risk factors were selected for pooling, including major resection, ASA classification of ≥3, advanced age, and male gender. Major resection and ASA ≥ 3 were identified as statistically significant factors of ERAS failure. Conclusion The comprehensive literature review results indicated that the frequently identified risk factors for ERAS failure after hepatic surgery are linked to operative and anesthesia factors, including substantial resection and an American Society of Anesthesiologists score of 3 or higher. These insights will assist healthcare practitioners in taking prompt remedial measures. Nevertheless, there is a requirement for future high-quality randomized controlled trials with standardized evaluation frameworks for ERAS programs.